TGF-β2-modulating Anti-apoptosis Effect of Osteoblasts by Sodium Fluoride - Yang, Jitao; Liu, Jialu; Xie, Xuyang; Deng, Qiang (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: This study aimed to investigate and discuss the mechanism of fluoride-induced osteoblast apoptosis in TGF-β2 signaling pathway. Materials and Methods: The osteoblasts were divided into 0 (control group), 5.0, 10.0, 20.0, and 40.0 mg/L sodium-fluoride induction groups, and the cells were collected after 24 hr and 48 hr induction (T1 and T2, respectively) to detect the changes in the mitochondrial-apoptosis pathway-related molecules (FoxO1, BAD, BCL-XL, BCL-2, and BAX). At the same time, the apoptosis index of fluoride-exposed osteoblasts was detected by flow cytometry. Results: The expression of TGF-β2 in the osteoblasts decreased with the increase in fluoride dose at T1 and T2. The expression levels of FoxO1 increased significantly at T1 and T2 in each dose group except for the 40 mg/L group (which had decreased expression). The expressions of p-BAD, BCL-XL, BCL-2, BAX, and other molecules increased with the increase in fluoride dose and exposure time. Conclusion: Fluoride can directly activate the TGF-β2 signaling molecules in osteoblasts and affect apoptosis. TGF-β2 plays an anti-apoptosis role in fluoride-exposed osteoblasts through the mitochondrial-apoptosis pathway.
Keywords: TGF-β2; Fluorosis; Mitochondrial Apoptosis; Osteoblasts; Signaling pathway